2011
DOI: 10.1177/1933719110382581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Triclocarban on Intact Immature Male Rat: Augmentation of Androgen Action

Abstract: Triclocarban (TCC; 3,4,4′-trichlorocarbanilide) is an antimicrobial agent used widely in various personal hygiene products including soaps. Recently, TCC has been shown to enhance testosterone-induced effects in vitro and to enlarge accessory sex organs in castrated male rats. This study was designed to evaluate the effects of TCC on intact age matched male rats and on human prostate LNCaP and C4–2B cells. Seven-week old male Sprague-Dawley rats received either a normal diet or a diet supplemented with TCC (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Enhancement was typically in the range of 20% to 40%, a finding confirmed in subsequent studies (34,35,63). In vivo studies using castrated male rats found that exposure to TCC and testosterone together significantly increased the weights of several male sex accessory organs and reproductive tract tissues relative to exposure to testosterone alone (34,35). Our work using zebrafish embryos confirms that TCC has enhancing effects on estrogen-stimulated gene transcription and provides a demonstration that TCC can enhance expression of a well-established, physiologically relevant estrogen target gene in vivo.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Enhancement was typically in the range of 20% to 40%, a finding confirmed in subsequent studies (34,35,63). In vivo studies using castrated male rats found that exposure to TCC and testosterone together significantly increased the weights of several male sex accessory organs and reproductive tract tissues relative to exposure to testosterone alone (34,35). Our work using zebrafish embryos confirms that TCC has enhancing effects on estrogen-stimulated gene transcription and provides a demonstration that TCC can enhance expression of a well-established, physiologically relevant estrogen target gene in vivo.…”
Section: Discussionsupporting
confidence: 65%
“…One micromolar of TCC by itself had little agonist activity toward any of these receptors but enhanced hormone-dependent induction of ER-and AR-dependent transcription of reporter constructs in cell-based assays. Enhancement was typically in the range of 20% to 40%, a finding confirmed in subsequent studies (34,35,63). In vivo studies using castrated male rats found that exposure to TCC and testosterone together significantly increased the weights of several male sex accessory organs and reproductive tract tissues relative to exposure to testosterone alone (34,35).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Interaction with endogenous hormones to potentially affect development of sex organs and interfere with reproduction has also been reported [912]. In cells, exposure to TCC at micromolar concentrations has been shown to enhance estradiol or testosterone dependent activation of estrogen and androgen responsive genes [9].…”
Section: Introductionmentioning
confidence: 99%
“…This stemmed from TCC's apparent ability to enhance hormone-dependent induction of estrogen receptor (ER)-and androgen receptor (AR)dependent gene expression in vitro [13][14][15][16]. In vivo studies in rats have supported the in vitro evidence that TCC augments, but does not directly elicit, androgen action [14,17]. Similarly, in a previous study with fathead minnow, TCC (10 mg/L) enhanced 17b trenbolone (TRB)-induced formation of nuptial tubercles (a male secondary sex characteristic) in females exposed to mixtures of the 2 chemicals for 21 d [18].…”
Section: Introductionmentioning
confidence: 99%